Ruthenium(II)-Catalyzed Homocoupling of α-Carbonyl Sulfoxonium Ylides Under Mild Conditions: Methodology Development and Mechanistic DFT Study - Zhang, Maosheng; Zhang, Jinrong; Teng, Zhenfang; Chen, Jianhui; Xia, Yuanzhi (Frontiers in Chemistry, 2020)
A mild ruthenium(II)-catalyzed homocoupling of α-carbonyl sulfoxonium ylides was developed and the detailed mechanism was understood based on DFT calculations in the current report. The catalytic system utilizes the α-carbonyl sulfoxonium ylide as both the directing group for ortho-2 sp 2 C-H activation and the acylmethylating regent for C-C coupling. Various substituents are compatible in the transformation and a variety of isocoumarin derivatives were synthesized at room temperature without any protection. The theoretical results disclosed that the full catalytic cycle contain eight elementary steps, and in all of which the cationic Ru(II) monomer is involved as the catalytic active species. The acid additive is responsible for protonation of the ylide carbon prior to the intramolecular nucleophilic addition and C-C bond cleavage. Interestingly, the intermediacy of free acylmethylation intermediate or its enol isomer is not necessary for the transformation.